Kesulitan mahasiswa dalam membagi tugas kelompok sebagai efek terhadap perilaku social loafing - Wirayudha, Aditia; Firdaus, Firman Shakti; Maajid, Rafi Ariq; Nurfarida, Firda; Santosa, Muhammad Iqbal (Academy of Education Journal, 2024)
Groups, comprising two or more interacting individuals, exert mutual influence on each other's behavior. This influence can be both positive and negative, affecting group cohesion. Negative effects may include dysfunctions like special interests, norm violations, role ambiguity, and kemalasan sosial. Social loafing involves an individual reducing effort when working collectively with others. It's a habitual behavior where one person's low contribution influences others. The study aims to investigate how difficulty in task distribution influences perceived inequality in contributions. Hypotheses were formulated to test the influence of Costs/Inconvenience, Coercion, and their combined effect on Kemalasan sosial. Results showed a significant positive influence of Costs/Inconvenience and Coercion on Social Loafing. Costs/Inconvenience had a greater individual impact. Respondents faced challenges in adjusting group work schedules, leading to rushed tasks and a perception of social loafing.